2021
DOI: 10.48048/wjst.2021.19814
|View full text |Cite
|
Sign up to set email alerts
|

Peak-to-Average Power Ratio reduction in Wavelet based OFDM using Modified Selective Mapping for Cognitive Radio Applications

Abstract: The prospect of guaranteed quality of service for primary and secondary users in the expression of regulated Peak-to-Average Power Ratio (PAPR) and Bit Error Rate (BER) can be increased in Cognitive Radios using Wavelet based OFDM systems which localize spectrum in realms of time and frequency. However, cutting the Gordian knot of high PAPR associated with the Multi-Carrier Modulation schemes to operate in the linear part of the power amplifier nourishing the balance between PAPR and BER is difficult. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In Sharma et al [18], They found that OFDM has many advantages compared to single carrier modulation, such as Immunity to impulse interference, high spectral density, resilience to radio frequency (RF) interference, resilience to channel fading, multipath resilience, and much lower complexity of the computational process. Arjun and Surekhe [19] studies the performance of PAPR related to OFDM and wavelet OFDM (WOFDM) using modified selective mapping (SLM). The authors address two problems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sharma et al [18], They found that OFDM has many advantages compared to single carrier modulation, such as Immunity to impulse interference, high spectral density, resilience to radio frequency (RF) interference, resilience to channel fading, multipath resilience, and much lower complexity of the computational process. Arjun and Surekhe [19] studies the performance of PAPR related to OFDM and wavelet OFDM (WOFDM) using modified selective mapping (SLM). The authors address two problems.…”
Section: Related Workmentioning
confidence: 99%
“…Different proposed techniques used for PAPR reduction are illustrated in [19][20][21][22][23], which are divided into three sets as shown in Figure 1. One of the simplest and most pragmatic approaches is clipping and filtering, which can limit the signal to the transmitter to eliminate the occurrence of high peaks above a certain level.…”
Section: Papr Reduction Techniquesmentioning
confidence: 99%
“…An alternative approach utilizes the Inverse Discrete Wavelet Packet Transform (IDWPT) and DWPT algorithms, employing Wavelet Packets (WPs) as subcarriers instead of IFFT/FFT, overcoming issues like high Peak-to-Average Power Ratio (PAPR) and bandwidth wastage [18][19][20], with added improvements possible through antenna diversity techniques [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, Selective mapping is a well-accepted method to reduce the PAPR in OFDM systems particularly in 5G systems. With nearly two decades, SLM has been studied and noticed and applied for various OFDM systems to combat the PAPR problems and developed a special SLM methods for the variants of them; Alamouti coded MIMO-OFDM system, downlink power domain OFDM-NOMA systems [7], UW-OFDM systems [8], waveletbased cognitive radio for OFDM system [9], and non-coherent OFDM-IM system [10].…”
mentioning
confidence: 99%